Modelo de mistura paramétrico com fragilidade na presença de covariáveis - Taconeli, João Paulo (Universidade Federal de São Carlos, 2013)
Some studies involving survival data are characterized by showing a significant proportion of censored data, that is, individuals who will never experience the event of interest, even if accompanied by a long period of time. For the analysis of long-term data, we presented the standard mixture model by Berkson & Gage (1952), where we assume the Weibull distribution for the lifetime of individuals at risk and covariate. The cure rate models implicitly assume that those individuals experiencing the event of interest possess homogeneous risk. Alternatively, we consider the standard mixture model with a frailty term in order to quantify the unobservable heterogeneity among individuals. This model is characterized by the inclusion of a unobservable random variable, which represents information that can not or have not been observed. We assume frailty with a gamma distribution, obtaining theWeibull stardanrd mixture model with frailty and covariates from a point of view parametric. We realized simulation studies with the purpose of analyzing the frequentists properties of estimation procedures. Applications to real data set showed the applicability of the proposed models in which parameter estimates were determined using the maximum likelihood and bayesian approaches.
Keywords: Análise de sobrevivência; Distribuição Weibull; Fragilidade; Modelo de mistura; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA